Rural-urban disparities in the associations of residential greenness with diabetes and prediabetes among adults in southeastern China - Yu, Wanqi; Li, Xiaoqing; Zhong, Wenling; Dong, Shu; Feng, Chuanteng; Yu, Bin; Lin, Xi; Yin, Yanrong; Chen, Tiehui; Yang, Shujuan; Jia, Peng (The Science of the total environment, 2023)
Greenness offers health benefits to prevent diabetes in urban areas. However, urban-rural disparities in this association have not been explored, with the underlying pathways understudied as well. We aimed to investigate and compare the associations and potential pathways between residential greenness and the risks for diabetes and prediabetes in urban and rural areas. Diabetes and prediabetes were diagnosed by fasting blood glucose (FBG). The participants' residential greenness exposure was estimated by the normalized difference vegetation index (NDVI) and enhanced vegetation index (EVI). The association of residential greenness with the risks for diabetes and prediabetes was estimated by logistic regression and the generalized additive model. The potential mediation effects of air pollution, body mass index (BMI), and physical activity (PA) were examined by causal mediation analysis. Of the 50,593 included participants, and the prevalence of prediabetes and diabetes were 21.22 % and 5.63 %, respectively. Each 0.1-unit increase in EVI500m and NDVI500m for healthy people reduced the risk for prediabetes by 12 % and 8 %, respectively, and substantially reduced the risk for diabetes by 23 % and 19 %, respectively. For those with prediabetes, each 0.1-unit increase in EVI500m and NDVI500m reduced the diabetes risk by 14 % and 12 %, respectively. Compared to the risks for diabetes at the 25th percentile of EVI500m/NDVI500m, such risks significantly reduced when EVI500m (NDVI500m) increased over 0.43 (0.48) and 0.28 (0.39) in urban and rural areas, respectively. The residential greenness-prediabetes/diabetes associations were mediated by air pollution and PA in urban areas and by air pollution and BMI in rural areas. Exposure to residential greenness was associated with a lower risk for prediabetes and diabetes in urban areas and, more strongly, in rural areas, which were partly mediated by air pollution, PA, and BMI. [Display omitted] •An increased level of residential greenness was associated with the decreased risk for prediabetes.•Residential greenness was more strongly associated with the risks for diabetes in rural than urban areas.•In urban areas, residential greenness did not reduce the risk for diabetes of those already at prediabetes status.•Mediation effects of air pollution, BMI, and physical activity varied by urbanicity and risk level of diabetes/prediabetes.•Diabetes risk significantly declined when EVI500m (NDVI500m) >0.43 (0.48) in urban areas and >0.28 (0.39) in rural areas.